2017
DOI: 10.1371/journal.pone.0179087
|View full text |Cite
|
Sign up to set email alerts
|

Loci associated with resistance to stripe rust (Puccinia striiformis f. sp. tritici) in a core collection of spring wheat (Triticum aestivum)

Abstract: Stripe rust, caused by Puccinia striiformis Westend. f. sp. tritici Erikss. (Pst) remains one of the most significant diseases of wheat worldwide. We investigated stripe rust resistance by genome-wide association analysis (GWAS) in 959 spring wheat accessions from the United States Department of Agriculture-Agricultural Research Service National Small Grains Collection, representing major global production environments. The panel was characterized for field resistance in multi-environment field trials and seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 73 publications
(83 reference statements)
6
40
0
1
Order By: Relevance
“…However, the latter four markers were mapped on 2BL at 595.0 to 696.7 Mb of 2B in this study ( Fig. This is also consistent with what Muleta et al (2017) found through genome-wide association mapping, which was that SNPs IWA3621, IWA2977, IWA4983, IWA4984, IWA5149, IWA6875, and IWA6818 linked to Yr QTL in TAM 111, UC1110, Opata 85, Louise, and IDO444 clustered at 189 MB, of which three SNPs (IWA2977, IWA6818, and IWA5149) were mapped in the same genetic region and IWA2977 was mapped next to the peak SNP (IWB47487) linked to QYr.tamu-2B (Supplemental Table S5, Fig. The flanking markers for this 2B major QTL from this study indicated that QYr.tamu-2B was located at the 154.3 Mb physical position on the Chinese Spring reference genome IWGSC RefSeq v1.0 (IWGSC, 2014), which is on 2BS instead of 2BL.…”
Section: Genetic Basis Of Stripe Rust Resistancesupporting
confidence: 90%
See 2 more Smart Citations
“…However, the latter four markers were mapped on 2BL at 595.0 to 696.7 Mb of 2B in this study ( Fig. This is also consistent with what Muleta et al (2017) found through genome-wide association mapping, which was that SNPs IWA3621, IWA2977, IWA4983, IWA4984, IWA5149, IWA6875, and IWA6818 linked to Yr QTL in TAM 111, UC1110, Opata 85, Louise, and IDO444 clustered at 189 MB, of which three SNPs (IWA2977, IWA6818, and IWA5149) were mapped in the same genetic region and IWA2977 was mapped next to the peak SNP (IWB47487) linked to QYr.tamu-2B (Supplemental Table S5, Fig. The flanking markers for this 2B major QTL from this study indicated that QYr.tamu-2B was located at the 154.3 Mb physical position on the Chinese Spring reference genome IWGSC RefSeq v1.0 (IWGSC, 2014), which is on 2BS instead of 2BL.…”
Section: Genetic Basis Of Stripe Rust Resistancesupporting
confidence: 90%
“…1C) were identified as flanking markers for Yr5. 1C) was reported to be close to the regions of Yr53 (5-11 cM) and Yr43 (9-18 cM) by Muleta et al (2017). PI 480148 showed resistance in all seeding tests to several predominant Pst races in the United States.…”
Section: Genetic Basis Of Stripe Rust Resistancementioning
confidence: 78%
See 1 more Smart Citation
“…The prospect of developing varieties with complex resistance backgrounds is increasingly facilitated by the capacity for developing high‐density molecular markers to perform genome‐wide association mapping that has a higher mapping resolution and genome‐wide prediction, which are more feasible due to the recent availability of genotyping‐by‐sequencing (Davey et al., 2011; Poland, Brown, Sorrells, & Jannink, 2012) and high‐density single nucleotide polymorphism (SNP) genotyping platforms (Cavanagh et al., 2013; Wang et al., 2014). In particular, the Illumina iSelect 9K and 90K wheat SNP chip assays have enabled robust and affordable genotyping of wheat and were successfully used for genome‐wide association mapping, linkage mapping, and genome‐wide predictions of various traits (Bajgain et al., 2015; Bulli, Zhang, Chao, Chen, & Pumphrey, 2016; Kertho, Mamidi, Bonman, McClean, & Acevedo, 2015; Maccaferri et al., 2015b; Muleta et al., 2017a,b; Naruoka et al., 2016; Turner et al., 2017; Wu et al., 2015). The objectives of this study were (i) to explore genetic diversity among accessions in a worldwide collection of winter wheat accessions and identify new sources of seedling and adult plant resistance to stripe rust, and (ii) to identify genomic regions underlying resistance to stripe rust in the winter wheat accessions through genome‐wide association analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Новым методическим подходом является полногеном ный поиск ассоциаций (genome wide association study -GWAS), который позволяет в геномах культивируемых сортов идентифицировать генетические локусы как с главными, так и с минорными эффектами (Gao et al, 2016;Gerard et al, 2017;Muleta et al, 2017). В качестве дополнительного преимущества этого метода отметим де тальную информацию по генотипированию сортов и се лекционных линий большим числом молекулярных мар керов и возможность применения этих данных для се лекции по большому числу признаков.…”
Section: перспективы использования чужеродных генов для создания устоunclassified